BUDAYA LITERASI MEMBACA DAN MENULIS MAHASISWA DI PERGURUAN TINGGI DI ERA DIGITAL SOCIETY 5.0 - Rossa, Rona (LP2M Universitas Adzkia, 2022)
To be able to participate and take part in the digital society 5.0 era, universities must focus on three main areas: basic literacy, competence, and character quality. The campus is an excellent place to cultivate reading and writing habits. However, these expectations have not been met in practice because students' interest in reading and writing remains low. The purpose of this research is to describe the literacy culture of Adzkia University students in terms of reading and writing. This study is a descriptive study. Questionnaires were distributed to students to gather information about their reading and writing habits. The collected data was then analyzed using descriptive methods. The study's findings revealed that students' literacy cultures had not developed optimally. It can be demonstrated that reading and writing literacy is still dominated in order for students to fulfill their obligations or assignments. Reading and writing are no longer a requirement, but rather an obligation. The two activities have not become a hobby or embedded as a culture of good behavior in the university environment. This is the result of two factors: internal factors and external factors. Lecture innovations and strategies, the preparation of facilities and infrastructure, and the use of technology to cultivate student literacy in reading and writing are very possible. So that students' reading and writing literacy culture can increase and students are able to compete in this digital society 5.0 era.